Revision of Australian Ectomocoris with the description of nine new species (Hemiptera: Heteroptera: Reduviidae) - Malipatil, M. B.; Liu, Yingqi; Cai, Wanzhi (Zootaxa, 2023)
The Australian species of the genus Ectomocoris Mayr, 1865 (Hemiptera: Heteroptera: Reduviidae: Peiratinae), are revised. A total of 13 species are recognised, including nine new species: E. binotatus Malipatil & Liu, sp. nov., E. borealis Malipatil & Liu, sp. nov., E. fuscatus Malipatil & Liu, sp. nov., E. fuscifemoralis Malipatil & Liu, sp. nov., E. interiorius Malipatil & Liu, sp. nov., E. latus Malipatil & Liu, sp. nov., E. luteolus Malipatil & Liu, sp. nov., E. major Malipatil & Liu, sp. nov. and E. spinosus Malipatil & Liu, sp. nov. Redescriptions of E. australicus (Reuter, 1881), E. decoratus (Stål, 1863), E. ornatus (Stål, 1863) and E. truculentus (Stål, 1863) are presented. Callisphodrus patricius Stål, 1867 is treated as a new junior synonym of E. ornatus (Stål, 1863). Lectotypes are designated for Eumerus (Eumerus) australicus Reuter, 1881, Pirates decoratus Stål, 1863, P. ornatus Stål, 1863, P. truculentus Stål, 1863 and C. patricius Stål, 1867. A key to species is provided together with images of dorsal habitus of males and females of different wing forms and major structures of the male genitalia to assist distinguishing these species. Based on morphology, brief comments are provided on putative species groups within the studied species. A male extragenital structure, present in almost half of the species studied, is described in detail and its potential value in diagnosis and analysis of phylogenetic relationships within the genus as well as between related peiratine genera is discussed.